Influence of the Index Card Match Learning Model on Student Learning Outcomes in the Social Sciences Subject - Usman, Usman; Yulia, Yulia; Musdalipa, Musdalipa (Journal of Education Method and Learning Strategy, 2026)
This study aims to determine the description of learning outcomes and the influence of the Index Card Match learning model on student learning outcomes in the subject of Social Studies on cultural heritage material for grade V of UPTD SD Negeri 12 Parepare. The approach used is a quantitative approach with a pre-experimental design experiment in the form of one group pretest-posttest design. The population in this study were all students at UPTD SD Negeri 12 Parepare, while the sample was 20 students of class VA. The research data were obtained from the results of the students' pretest and posttest. The results of the inferential statistical analysis with the Paired Samples T-test showed that sig. (2-tailed) = 0.00 <0.05, so H0 was rejected and Ha was accepted. This indicates a significant difference between student learning outcomes before and after the application of the Index Card Match learning model. Thus, the conclusion of this study is that there is a difference in the value of student learning outcomes before and after the application of the Index Card Match learning model in the subject of Social Studies for grade V of UPTD SD Negeri 12 Parepare.